New quinazolinone derivatives: Synthesis and in vitro cytotoxic activity - Thinh, Tran Dang; Thuy, Le Thi; Duc, Ta Hong; Vu, Tran Khac (Vietnam Journal of Science and Technology, 2020)
The paper presents a simple synthesis of new quinazolinone derivatives 13a-i. Synthesized derivatives were tested for their cytotoxic effect against three cancer cell lines including SKLU-1, MCF-7 and HepG-2. The bioassay result showed that only compound 13e exhibited significant cytotoxic effect against cancer cell lines tested with IC50 values of 9.48, 20.39 and 18.04 µg/ mL, respectively.